Device Model for Methylammonium Lead Iodide Perovskite With Experimentally Validated Ion Dynamics. (13th April 2020) - Sajedi Alvar, Mohammad; Blom, Paul W.M.; Wetzelaer, Gert‐Jan A. H.
Abstract: Being based on mixed ionic‐electronic semiconductors, the operation of perovskite solar cells depends on many parameters. To develop an experimentally validated numerical device model, it is therefore necessary to isolate individual physical phenomena. To this end, the dynamics of ion motion in lead halide perovskites is investigated by measuring impedance spectra and the electric displacement as a function of frequency in dark. The displacement response is fully reproduced by a numerical device model that combines electronic and ionic conduction. For a quantitative description of the displacement, it is critical to consider the frequency‐dependent apparent dielectric constant, the ion concentration and the ion diffusion coefficient. The numerical simulations enable to quantify the effect of ion motion and voltage scan speed on the electric field distribution in MAPbI3 based devices, laying the foundations for an experimentally validated perovskite device model. Abstract : Ion dynamics play an important role in metal halide perovskite solar cells. Here, a device model is developed for which the parameters of ion diffusion and concentration are experimentally validated, using two independent measurement techniques, viz. impedance spectroscopy and electric displacement measurements. The experimentally validated ion dynamics allow for simulation of the time‐dependent electric‐field distribution in solar cells.